Some Results on a Generalized Version of Congruent Numbers - Leomarich F. Casinillo; Emily L. Casinillo (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2021)
AbstractThis paper aims to construct a new formula that generates a generalized version of congruent numbers based on a generalized version of Pythagorean triples. Here, an elliptic curve equation is constructed from the derived generalized version of Pythagorean triples and congruent numbers and gives some new results.Keywords: Pythagorean triple, congruent number, elliptic curve equation. AbstrakArtikel ini bertujuan untuk mengkonstruksi formula baru yang membangun versi yang lebih umum dari bilangan-bilangan kongruen berdasarkan versi triple Pythagoras yang diperumum. Di sini, akan dikonstruksi suatu persamaan kurva eliptik dari triple Pythagoras dan bilangan-bilangan kongruen dalam versi yang diperumum untuk menghasilkan hasil-hasil yang baru.Kata kunci: triple Phytagoras, bilangan kongruen, persamaan kurva eliptik.2010 Mathematics subject classification: 11A07, 11A41, 11D45, 11G07.